Vertebral morphology in extant porpoises: Radiation and functional implications - Marchesi, María Constanza; Galatius, Anders; Zaffino, Martina; Coscarella, Mariano Alberto; Gonzalez-Jose, Rolando (Journal of Morphology)
Vertebral morphology has profound biomechanical implications and plays an important role in adaptation to different habitats and foraging strategies for cetaceans. Extant porpoise species (Phocoenidae) display analogous evolutionary patterns in both hemispheres associated with convergent evolution to coastal versus oceanic environments. We employed 3D geometric morphometrics to study vertebral morphology in five porpoise species with contrasting habitats: the coastal Indo-Pacific finless porpoise (Neophocaena phocaenoides); the mostly coastal harbor porpoise (Phocoena phocoena) and Burmeister's porpoise (Phocoena spinipinnis); and the oceanic spectacled porpoise (Phocoena dioptrica) and Dall's porpoise (Phocoenoides dalli). We evaluated the radiation of vertebral morphology, both in size and shape, using multivariate statistics. We supplemented data with samples of an early-radiating delphinoid species, the narwhal (Monodon monoceros); and an early-radiating delphinid species, the white-beaked dolphin (Lagenorhynchus albirostris). Principal component analyses were used to map shape variation onto phylogenies, and phylogenetic constraints were investigated through permutation tests. We established links between vertebral morphology and movement patterns through biomechanical inferences from morphological presentations. We evidenced divergence in size between species with contrasting habitats, with coastal species tending to decrease in size from their estimated ancestral state, and oceanic species tending to increase in size. Regarding vertebral shape, coastal species had longer centra and shorter neural processes, but longer transverse processes, while oceanic species tended to have disk-shaped vertebrae with longer neural processes. Within Phocoenidae, the absence of phylogenetic constraints in vertebral morphology suggests a high level of evolutionary lability. Overall, our results are in accordance with the hypothesis of speciation within the family from a coastal ancestor, through adaptation to particular ...